2017
DOI: 10.1002/hep4.1029
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA therapy inhibits hepatoblastoma growth in vivo by targeting β‐catenin and Wnt signaling

Abstract: Hepatoblastoma (HBL) is the most common pediatric liver cancer. In this malignant neoplasm, beta‐catenin protein accumulates and increases Wnt signaling due to recurrent activating mutations in the catenin‐beta 1 (CTNNB1) gene. Therefore, beta‐catenin is a key therapeutic target in HBL. However, controlling beta‐catenin production with therapeutic molecules has been challenging. New biological studies could provide alternative therapeutic solutions for the treatment of HBL, especially for advanced tumors and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…Statistical analyses were performed using GraphPad Prism 6.0 software as described. (17) See Supporting Information for further methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses were performed using GraphPad Prism 6.0 software as described. (17) See Supporting Information for further methods.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were recruited in accordance with European and French law and institutional ethical guidelines . A set of 73 liver samples (44 HB and 29 nontumoral [NT] liver including 29 pairs of tumor and adjacent NT liver) was collected from 39 patients treated at French university hospitals or from the SIOPEL Liver Tumor and Tissue Bank (http://www.siopel.org).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Similarly, miR-449b-5p has been reported to be under-expressed in liver cancer and inhibits cell proliferation and cell migration. 19 The 3 0 -UTR of HMGB1 contains the site for miR-449b-5p binding, and therefore, miR-449b-5p has been predicted to be involved in the hepatic I/R injury by controlling HMGB1 and can be a potential target in the effective treatment of liver diseases. 20 However, unmodied miRNA is highly unstable in the systemic circulation due to its enzymatic degradation, resulting in its poor therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…RAF1 reduction mediated by let‐7i‐3p plays a role in melatonin inhibition of hepatocellular carcinoma . Indersie et al reported that let‐71‐3p, miR‐449b‐3p, and miR‐885‐5p were decreased in tumors compared to normal livers, and that these miRNAs inhibited HBL cell grow and Wnt signaling activity in vitro, partly through beta‐catenin downregulation . Some studies predicted the potential target genes of let‐7i‐3p and its involvement in various cellular pathways .…”
Section: Discussionmentioning
confidence: 99%